2015
DOI: 10.1016/j.bbrc.2015.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide N-methyltransferase increases complex I activity in SH-SY5Y cells via sirtuin 3

Abstract: Nicotinamide N-methyltransferase (NNMT, E.C. 2.1.1.1) N-methylates nicotinamide to 1-methylnicotinamide. We have previously shown that NNMT is significantly overexpressed in the brains of patients who have died of Parkinson's disease, and others have shown that NNMT is significantly overexpressed in a variety of diseases ranging from cancer to hepatic cirrhosis. In vitro overexpression has revealed many cytoprotective effects of NNMT, in particular increased complex I activity and ATP synthesis. Although this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 34 publications
0
48
0
Order By: Relevance
“…SIRT3 expression was knocked down using SIRT3-targeting siRNA (sc-61555; Santa Cruz Biotechnology, Santa Cruz, CA, USA) as described. 26 A scrambled-sequence siRNA (sc-37007; Santa Cruz) served as negative control. HK2 cells were transfected with these siRNAs using Entranster TM -R transfection reagent (Engreen Biosystem, Beijing, China).…”
Section: Sirt3 Knockdown and Overexpression In Vitromentioning
confidence: 99%
“…SIRT3 expression was knocked down using SIRT3-targeting siRNA (sc-61555; Santa Cruz Biotechnology, Santa Cruz, CA, USA) as described. 26 A scrambled-sequence siRNA (sc-37007; Santa Cruz) served as negative control. HK2 cells were transfected with these siRNAs using Entranster TM -R transfection reagent (Engreen Biosystem, Beijing, China).…”
Section: Sirt3 Knockdown and Overexpression In Vitromentioning
confidence: 99%
“…Although NNMT is mainly expressed in the liver in healthy tissues [17,18] low NNMT expression has been detected in the brain, lung, heart, kidney, skeletal muscle and placenta [7]. In contrast, high expression is reported in the cerebellum and caudate nucleus of patients who have succumbed to Parkinson's disease (PD), and also in many other diseases including osteoarthritis, cirrhosis, chronic obstructive pulmonary disease, cardiovascular disease and cancer [19]. Most importantly, reports indicate that NNMT expression is significantly increased in tumors [20].…”
Section: Nnmt Expressionmentioning
confidence: 99%
“…While further experimentation demonstrated that NNMT expression in SH-SY5Y cells notably induced the expression of all three sirtuins (SirTs), siRNA-mediated silencing of SirT3 expression decreased CxI activity and significantly reduced cellular ATP content. [19] Colorectal cancer. Colorectal cancer (CRC) is one of the most common malignancies in the world and it continues to be a serious public health concern [31].…”
Section: Role Of Nnmt In Cancermentioning
confidence: 99%
“…[1][2][3][4] In this regard, the overexpression of NNMT has recently been shown to cause AdoMet depletion in cancer cells. 5 Other studies have suggested a role for NNMT as a cytoprotective agent in Parkinson's disease [6][7][8] while other findings point to a potential link between MNA and lifespan regulation. 9 In addition, the upregulation of NNMT is observed in a range of metabolic disorders including diabetes and obesity.…”
Section: Introductionmentioning
confidence: 99%